MHD Free Convective Heat and Mass Transfer Flow from a Vertical Porous Surface with Variable Thermal Conductivity, Variable Mass Diffusivity and Thermal Diffusion Including Viscous Dissipation and Chemical Reaction - J. Phakirappa; S. Priyanka; P.H. Veena; V.K. Pravin (International Journal of Applied Mechanics and Engineering, 2022)
An analysis is carried out to study chemically reactive, viscous dissipative effects of an incompressible and electrically conducting fluid with MHD free convection adjacent to a vertical surface with variable thermal conductivity (VTD) and variable mass diffusivity (VMD). An approximate numerical solution for the steady laminar boundary layer flow over a wall of the surface in the presence of species concentration and thermal mass diffusion has been studied. Using numerical techniques the governing boundary layer equations are solved to get the exact solution. Numerical calculations are carried out for different values of dimensionless parameters. The results are exhibited through various graphs and it is observed from the analysis of the results that the velocity field is appreciably influenced by the magnetic effect, porous effect, chemical reaction and buoyancy ratio between the species and thermal diffusion at the wall of the surface.